2016
DOI: 10.1007/s13277-015-4742-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic serum levels of EGFR and ErbB2 and genetic glioma risk variants: a nested case-control study

Abstract: Genetic variants have been associated with the risk of developing glioma, but functional mechanisms on disease phenotypic traits remain to be investigated. One phenotypic trait of glioblastoma is the mutation and amplification of the epidermal growth factor receptor (EGFR) gene. We investigated associations between pre-diagnostic serum protein concentrations of EGFR and ErbB2, both members of the EGFR family, and future risk of glioma. Further, we studied if EGFR glioma risk variants were associated with EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…One hypothesis of the link between genetic variants and the risk of subtype-specific disease could be that the genetic variants convey their increased glioma risk through contributing to a chronical activation of the EGFR receptor family that triggers tumor initiation. This is supported by the observation that glioma cases had higher concentrations of sEGFR and sERBB2 protein levels in prediagnostic serum samples from individuals that later developed GBM compared to matched controls [31,32]. In the brain tissue eQTL results, we found that risk variant of rs723527, located in intron 1, was associated with lower levels of EGFR expression.…”
Section: Idh-wildtype Glioma Risk Variantssupporting
confidence: 60%
“…One hypothesis of the link between genetic variants and the risk of subtype-specific disease could be that the genetic variants convey their increased glioma risk through contributing to a chronical activation of the EGFR receptor family that triggers tumor initiation. This is supported by the observation that glioma cases had higher concentrations of sEGFR and sERBB2 protein levels in prediagnostic serum samples from individuals that later developed GBM compared to matched controls [31,32]. In the brain tissue eQTL results, we found that risk variant of rs723527, located in intron 1, was associated with lower levels of EGFR expression.…”
Section: Idh-wildtype Glioma Risk Variantssupporting
confidence: 60%
“…Another commonly noted feature of glioblastoma is the mutation and amplification of the EGFR gene [ 28 ]. The aberrant EGFR-mediated oncogenic signaling is found in glioblastoma [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several of the enriched pathways were associated with tumorigenesis, including ErbB, mTOR and cell cycle signaling pathways. The ErbB pathway is associated with tumor progression in the majority of cancer types, including glioma (36,37). Furthermore, Table II.…”
Section: Discussionmentioning
confidence: 99%